ANALISIS TEKS PERSUASI KARYA SISWA KELAS VIII SMP NEGERI 9 MAROS: Analysis of Persuasive Texts Written by Students in Grade VIII of Smp Negeri 9 Maros - Nurwahida; Salam; Sultan (Journal of Applied Linguistics and Literature, 2025)
This study aims to describe the structure of persuasive text and the linguistic characteristics of persuasive text by students of class VIII SMP Negeri 9 Maros. This type of research is descriptive qualitative research. The focus of this research is the structure of persuasive text and the linguistic characteristics of persuasive text. The research data source is persuasive text by students. The data collection technique was carried out using the mark reading technique and the note taking technique. The instrument of this research is the researcher himself as the main instrument and supporting instruments such as documentation studies in the form of students' persuasive text work. The results of this study prove that, mastery of the structure of persuasive text and the linguistic characteristics of persuasive text is still weak which is characterized by the incomplete structure and lack of linguistic features in the work of persuasive text.